Dermatopathia Pigmentosa Reticularis with Salzmann’s nodular degeneration of cornea: A rare association - Goel, R; Bodh, S A; Sardana, K; Goel, A (Nepalese Journal of Ophthalmology, 2015)
Background: Dermatopathia pigmentosa reticularis (DPR) is a very rare autosomal dominant disorder with the diagnostic triad of generalized reticulate hyperpigmentation, noncicatricial alopecia and onychodystrophy. Objective: To describe the occurrence of Salzmann’s nodular degeneration of cornea with moderate dry eye in a patient with Dermatopathia pigmentosa reticularis.Case: We present an 11 year old young Indian girl with DPR who had Salzmann’s nodular degeneration of cornea with moderate dry eye. She was put on symptomatic treatment and counseled regarding the course of disease, familial nature and avoidance of exposure to sun. Conclusion: In a patient of Salzmann`s nodular degeneration with generalized reticulate hyperpigmentation, noncicatricial alopecia and onychodystrophy the diagnosis of DPR must be kept in mind. A multidisciplinary approach is required for the management of such cases.